Development of Human Resources Apparatus at the Personnel and Human Resources Development Agency (BKPSDM) of East Bolaang Mongondow Regency - Pakaya, Kasmat Priana (JISIP: Jurnal Ilmu Sosial dan Pendidikan, 2024)
This research aims to find out what efforts have been made in the Development of Human Resources of the Apparatus as well as obstacles that become obstacles in the implementation of Human Resources Development of the Apparatus at the Personnel and Human Resources Development Agency.This research uses descriptive qualitative methods, aimed at describing and describing existing phenomena, both natural and human engineering, which pay more attention to the characteristics, quality and interrelationships between activities. Collection techniques were carried out through observation, interviews and document review. Then the data is analyzed using data analysis steps carried out by reducing research data, displaying data, drawing conclusions and triangulating research data.The focus of this research is the implementation of apparatus human resource development, namely the implementation of technical education and training and the implementation of structural managerial education and training at the Staffing Agency and Human Resources Development of East Bolaang Mongondow Regency. Based on the results of the research conducted, it is concluded that the implementation of human resource development of the apparatus, namely the implementation of technical education and training and managerial structural education and training at the Staffing and Human Resources Development Agency (BKPSDM) of East Bolaang Mongondow Regency is not optimal with several obstacles.